Pemaknaan Lagu â€œLir-Ilirâ€ Karya Sunan Kalijaga Sebuah Analisis Semiotik Saussure - nikendwipuspitasari (Balai Bahasa Provinsi Riau, 2024)
The purpose of this research is to reveal the real meaning behind the lyrics of the song